A Study of Common Diagnostic Methods for Determining Antibiotic Residues in Milk - Sarwary, Nasir Ahmad (Journal of Natural Sciences – Kabul University, 2024)
The unauthorized use of antibiotics in milk poses significant risks to human health and contributes to microbial resistance. Most milk consumed comes from cows, some of which may be treated with antibiotics. This study aims to explore methods for detecting antibiotics in milk and to assess the adverse effects of contaminated milk. The research employs a review method, revealing that while immunochemical, chromatography, and spectrometry methods are highly accurate, their high costs and time demands limit their use. In contrast, microbiological, enzymatic, and biochemical methods are more widely utilized, with various kits developed based on these techniques. Moreover, biosensor technologies are emerging as innovative methods with promising potential, and Marking method serve a preventive role. In conclusion, a variety of methods for antibiotic detection in milk have been developed, each with unique advantages, highlighting the importance of addressing antibiotic contamination for public health safety.